2004
DOI: 10.1002/ab.20006
|View full text |Cite
|
Sign up to set email alerts
|

Friendship and loneliness among bullies and victims: Data from seven countries

Abstract: Research suggests that the relationship between school bullying and its various risk factors should be clearer among girls than boys, and should become stronger with age, as roles within the peer group stabilise. This paper tests this theory by comparing sex, school type, and bully/victim status differences in friendships and playground social interactions, using data from nine surveys in seven countries: China, England, Ireland, Italy, Japan, Portugal, and Spain. A total of approximately 48,000 children compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
155
1
15

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 236 publications
(185 citation statements)
references
References 26 publications
12
155
1
15
Order By: Relevance
“…Adolescents who scored +1 SD on bullying and lower than +1 SD on victimization were dropped from further analyses since they represented the bullies (n = 263, 11% of the original sample), while our study focused on victims and used the non-involved adolescents as the control group. The prevalence rates of victims, bully-victims, and non-involved adolescents in our study are comparable to prevalence rates reported in other studies (e.g., Eslea et al 2003;Nansel et al 2001;Salmivalli and Nieminen 2002).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Adolescents who scored +1 SD on bullying and lower than +1 SD on victimization were dropped from further analyses since they represented the bullies (n = 263, 11% of the original sample), while our study focused on victims and used the non-involved adolescents as the control group. The prevalence rates of victims, bully-victims, and non-involved adolescents in our study are comparable to prevalence rates reported in other studies (e.g., Eslea et al 2003;Nansel et al 2001;Salmivalli and Nieminen 2002).…”
Section: Resultssupporting
confidence: 90%
“…Bullying in school is a major problem that affects many children, with prevalence rates ranging from 5 to 26% in Western and Non-Western countries (Eslea et al 2003;Smith et al 1999). During the last decade, bullying is increasingly viewed as a social group phenomenon, and the role of friends has become an important focus of attention.…”
mentioning
confidence: 99%
“…Borntrager et al 2009;Eslea et al 2004). Smith and Sharp (1994) define bullying as 'a systematic abuse of power' (2).…”
mentioning
confidence: 99%
“…Bullying is a pervasive problem in Swedish schools as well as in schools in other countries in Europe, America, Asia, and Australia (e.g., Borntrager, Davis, Bernstein, & Gorman, 2009;Eslea et al, 2003;Smith et al, 1999). It is a phenomenon that affects a lot of students.…”
mentioning
confidence: 99%